The Influence of Cash Flow, Net Profit and Company Size on Stock Prices in Food and Beverage Companies Listed on the Indonesia Stock Exchange (BEI) Period 2018 - 2022 - Khofifah, Resti (Green Publisher Indonesia, 2024)
This study aims to empirically prove the effects of cash flow, net income, and company size on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The population in this study consists of 48 food and beverage companies. The sampling technique used is purposive sampling, based on predetermined criteria, resulting in a sample of 18 companies over a five-year research period, totaling 90 samples. The analytical method employed is quantitative analysis using multiple linear regression, t-tests, and F-tests with the assistance of SPSS 26. The results indicate that, partially, cash flow has no significant effect on stock prices, net income has a positive and significant effect on stock prices, and company size has a negative and insignificant effect on stock prices. Furthermore, simultaneously, cash flow, net income, and company size have a positive and significant effect on stock prices.